2014
DOI: 10.1057/jit.2013.26
|View full text |Cite
|
Sign up to set email alerts
|

Can Customer Satisfaction and Dissatisfaction Coexist? An Issue of Telecommunication Service in China

Abstract: Although the telecommunication industry in China is growing at a fast pace, and firms are making strong efforts to provide customers with various services, customer switching continues to be high. Satisfaction has been considered as one of the most important antecedent of customer loyalty. However, little attention has been paid to dissatisfaction, a qualitatively different construct from satisfaction, which also influences loyalty. Relying on the two-factor and three-factor theory, this research proposes a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 57 publications
(97 reference statements)
3
32
1
4
Order By: Relevance
“…Study by Chen et al (2014) and Khan and Afsheen (2012) found that network quality has significant positive influence on customer satisfaction which is not true for this study. In the context of Bangladesh, this study confirms the conclusion of Hossain and Suchy (2013) satisfaction is the prime determinant of customer retention.…”
Section: Discussion and Managerial Implicationscontrasting
confidence: 66%
See 1 more Smart Citation
“…Study by Chen et al (2014) and Khan and Afsheen (2012) found that network quality has significant positive influence on customer satisfaction which is not true for this study. In the context of Bangladesh, this study confirms the conclusion of Hossain and Suchy (2013) satisfaction is the prime determinant of customer retention.…”
Section: Discussion and Managerial Implicationscontrasting
confidence: 66%
“…Researchers have identified the association between network service quality and its consequences on customer satisfaction. Chen et al (2014) pointed that due to low quality of network, consumers become dissatisfied which lead them to switch other network operators. Additionally, poor network superiority tends to lower customer satisfaction toward the mobile service operator, thus it causes increased number of customer complaints (Chen et al, 2011).…”
Section: Network Qualitymentioning
confidence: 99%
“…This probably originates from the misconception that these two terms, satisfaction and dissatisfaction, are two sides of the same coin; but they are not. Past research has stressed that they are two different and independent entities that can even coexist (Chen, Lu, Gupta, & Xiaolin, 2013;Lee et al, 2010;Srijumpa, Chiarakul, & Speece, 2007). According to the two-factor theory developed by Herzberg and Mausner (1959) satisfaction and dissatisfaction are two distinct concepts originating from different interactions of customers and product/service.…”
Section: Satisfaction Vs Dissatisfactionmentioning
confidence: 99%
“…Para Patil y Patil (2014), la decisión acerca de qué servicios externalizar debe centrarse en una búsqueda de mejores ventajas competitivas y no de costos, es decir, que el fin de la tercerización debe ser cederle la administración de un determinado servicio a otra empresa que tenga la habilidad de realizar mejor esta tarea que la misma empresa de telecomunicaciones y así esta última pueda enfocarse en buscar mejoras para aquellos servicios que sí sean fundamentales en su negocio. servicio que no varían en gran medida entre las demás empresas proveedoras de este tipo de servicio (Chen et al, 2014). En cuanto a los factores motivacionales en estudio, se comprobó que la capacidad de manejo de reclamos influye directamente en la lealtad del cliente.…”
Section: Gestión De Los Servicios En Las Telecomunicacionesunclassified
“…Asimismo, se comprobaron verdaderas las 5 hipótesis principales del estudio donde se destaca que las empresas del sector de telecomunicaciones pueden realizar 2 tipos de enfoque: Pueden analizar los factores que afectan la percepción motivacional de los clientes para lograr su satisfacción o estudiar los factores que afectan la percepción funcional de los clientes a fin de predecir y evitar la insatisfacción de los mismos. Ambos tipos de enfoque permitirán generar la lealtad de los clientes (Chen et al, 2014).…”
Section: Gestión De Los Servicios En Las Telecomunicacionesunclassified